Protoype Prediksi Persediaan Menggunakan Metode Weight Moving Average - Fitri Purwaningtias; Muhamad Ariandi; Suyanto (SOTVI - Society of Visual Informatics, 2023)
PT. In inventory, companies often experience excess spare parts they have or shortages of spare parts that many consumers need. So sometimes the warehouse is overloaded or empty of goods that are in high demand. To overcome this warehouse inventory problem so that there are no overloads or empty items, it is necessary to predict inventory in the warehouse using the weight moving average (WMA) method and also a system development method using the prototype method. This prediction system is used to find out which items are in demand and which are less needed so that the warehouse can be used optimally. In this research, it was found that predictions using WMA can help company performance based on the user testing methods that have been carried out so that it is feasible for companies.